Lasing Characteristics of Optical Thyristor for Optical Logic Function - Kim, D.; Lee, H.; Choi, W.; Choi, Y.; Lee, S.; Woo, D.; Byun, Y.; Kim, J.; Kim, S.; Nakano, Y. (Conference on Optical Fiber Communication, Technical Digest Series, 2003)
The waveguide-type depleted optical thyristor laser diode with InGaAs/InGaAsP MQW structure was demonstrated. To increase the efficiency of optical emission the single quantum well undoped laser was incorporated in the active layer of the WDOT-LD, to gave lasing characteristics at a wavelength of 1.5μM. The waveguide-type PnnN optical thyristors showed the nonlinear s-shape I-V and lasing characteristics. The lasing threshold current at 25°C and 10°C were 111 mA and 72.5 mA.